PREPARING PBT TOEFL PREDICTION: AN EXPERIENCE OF ONLINE TEACHING TOEFL PREPARATION - Abdulloh Abdulloh; Sarsono Sarsono; Slamet Basuki (STIBA IEC JAKARTA, 2021)
This study is aimed at exploring procedure, and teaching resources prepared by teachers on preparing the PBT TOEFL prediction at STIKES Banisaleh. There are 50 students joining the TOFL preparation course seated in different classes. This study has two research questions; a) How the teaching team use the certain procedure to prepare PBT TOEFL test in online way, b) What varied online teaching resources are applied by team teaching. Descriptive qualitative method is used to analyze the certain procedure and the varied resources used by the teaching team. Questionnaire distributed after the diagnostic test to investigate and prove the student’s preferences of study matched with the teacher’s procedures. Then researcher with the teaching team applied certain procedure. It is preceding Section Two of TOEFL PBT - Structure and Written Expression, then section three – Reading Comprehension, the last Listening Comprehension. And varied online teaching resources also made to accomplish the teaching procedure. It shows that the average score of the PBT TOEFL prediction at STIKES Banisaleh is 400. It means that Preparing PBT TOEFL by preceding Section Two and using varied online teaching resources is effective